Systematic Review from Different Encryption Techniques Perspectives - alsadig abdallah; Amir Talib; Mandour Ibrahim; Elhadi AbdElgader (International Journal of Advanced Science and Computer Applications, 2024)
The volume of Big Data produced from various sources is always growing. Such vast amounts of data cannot be stored using conventional techniques. As a result, the majority of businesses have switched to using cloud storage as a substitute for storing Big Data. Cloud storage has made great progress, but there are still several problems, such security worries. This article examines Big Data, its difficulties, and many security concerns from the perspectives of various encryption approaches. Additionally, it presents various views to address these issues and suggests a new classification of Big Data security difficulties